Contractile and mechanical properties of hamstring muscles measured by the method of tensiomyography (TMG) in professional soccer players: A systematic review, meta-analysis and meta-regression - Fernández-Baeza, D.; González-Millán, C.; Díaz-Ureña, G. (PLOS ONE, 2025)
Tensiomyography (TMG) is a non-invasive device used to assess contractile and mechanical properties during an isometric muscle contraction. The purpose of this systematic review was two-fold: 1) to know the scientific evidence of hamstring muscles TMG parameters in professional football players during the competitive season, and 2) to establish the most-frequent values for the main TMG parameters in soccer players compared with the reference values of the TMG software. PRISMA guidelines were followed, and a systematic search was performed in the PubMed, Web of Science, and Sport Discus electronic databases with no date restrictions until November 2023. The studies considered for this meta-analysis were studies investigating professional soccer players between 20- and 29-years measured during the competitive season and reported tensiomyography-derived parameters such as contraction time and/or maximal displacement, and/or delay time, of the hamstring muscles (biceps femoris and semitendinosus). A total of 139 studies were identified and 12 studies were included in the systematic review and for the meta-analysis. All studies underwent a quality assessment using the Newcastle-Ottawa scale, and the NOS score varied from 7/9 to 8/9 in all studies, suggesting a good quality of all articles. Study results were analyzed using restricted maximum-likelihood and random-effects models. The main findings of the study are that of the six parameters analysed, three variables were found to differ significantly. Furthermore, the weighted mean values founded were biceps femoris (Tc 27.88, Dm 5.2, Td 23.72) and in semitendinosus (Dm 8.72, Td 25.25). TMG can serve as a valuable device for assessing neuromuscular function in soccer players. Furthermore, shows the most-frequent values of the biceps femoris and the semitendinosus, where different values in the TMG parameters can be observed between the synergistic muscles.